Pengaruh Digital Service dan Tingkat Kemudahan Terhadap Minat Bertransaksi Nasabah di Pegadaian UPC Buluran Kenali - Tri Nabila; Novi Mubyarto; Anzu Elvia Zahara (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study is to examine the influence of digital services and the level of convenience on customer transaction interest at the Buluran Kenali UPC pawnshop. This quantitative study utilized a total sampling method with 77 respondents from customers at the Buluran Kenali UPC pawnshop. This research provides a practical contribution to Pegadaian management in improving digital services with the G-5Star Generation strategy, enabling the pawnshop to transform the company into a financial company. With the launch of the Pegadaian Digital Service (PDS) application, the company aims to expand its target market to the millennial generation. In the inferential statistical analysis stage, data analysis was assisted by statistical programs using SEM, specifically the Smart-PLS analysis computer program. The data collection method used a questionnaire. The results of this study are: 1) there is a significant and positive effect of digital services on customer transaction interest at the Buluran Kenali UPC pawnshop. 2) there is no significant effect of the level of convenience on customer transaction interest at the Buluran Kenali UPC pawnshop.